Drip fungigation in early blight control of tomato - doi: 10.4025/actasciagron.v33i1.9515 (Acta Scientiarum. Agronomy, 2011)
The aim was to verify if the fungigation via drip irrigation is an alternative to the conventional method of spraying on tomato for controlling early blight. Tomato plants (variety Santa Clara) were grown in pots inside a greenhouse. Fifty days after transplanting, the plants were inoculated with Alternaria solani and treated with four different fungicides: azoxystrobin (8 g 100 L-1), difeconazole (50 mL 100 L-1), metiram+piraclostrobin (200 g 100 L-1) and tebuconazole (100 mL 100 L-1) using two applications methods: conventional spraying and fungigation dripping. The control plants did not receive fungicide application. To assess the severity of the disease, we used a rating scale expressed as the area under the disease progress curve (AUDPC) and production factors, such as number, weight and average diameter of the fruit and its productivity. The experimental design was completely randomized in factorial scheme 4 x 2 + 1 with eight replicates. Each plot had one plant in one pot. A 27% reduction in disease severity was observed when compared with the control plants, with no significant difference noted regarding the application method. The number of fruits did not statistically differ between the treatments. The average weight and diameter of the fruits were superior in the plants that had fungicide application compared to the control plant, reflecting an increase in productivity. Fungigation through water dripping is an alternative to the conventional method of spraying cultured tomatoes.